Periviable birth: Legal landscape in Indian jurisprudence - Shivashankar Diggikar; Karthik Nagesh; Nanditta Batra (BMJ Paediatrics Open)
Periviability represents a complex threshold where there is a triangulation of medical capabilities, ethical judgement and the right of the infant to live. In India, with its disproportionate burden of preterm births, the management of infants born at the margins of viability (typically <28 weeks of gestation) remains fraught with legal and ethical challenges. We critically explore the legal contours surrounding the care of periviable neonates from an Indian medico-legal perspective in this article. Despite lacking a uniform national consensus on viability thresholds, Indian jurisprudence confers personhood to neonates at birth, irrespective of gestational age, thereby guaranteeing constitutional protection under Article 21. However, in the absence of explicit guidelines and robust systemic infrastructure, physicians and families must navigate resuscitation decisions amid legal uncertainty, cost constraints and moral complexity. Judicial precedents have mandated life-saving interventions for viable neonates born alive post medical termination attempts, reinforcing the right to care. We discuss the limitations of legal doctrines such as parental autonomy, leave against medical advice and advance directives when applied to neonates who cannot consent for obvious reasons. We also highlight challenges arising from evolving tort liability, procedural lapses and resource inequity in neonatal care.